The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/0034-7167-2018-0231
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors for acute kidney injury in preterm infants

Abstract: Objective: to analyze the prevalence and factors associated with acute kidney injury in preterm newborns. Method: a cross-sectional study based on records data of preterm newborns hospitalized in two neonatal units in northwest Paraná State in 2015. For data analysis, the logistic regression model was used by the stepwise forward method and Fisher's Exact Test. Results: 132 preterm newborns, with a prevalence of 7.5% of acute kidney injury, were hospitalized. Majority of males, extremely preterm and very low b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
0
1
1
Order By: Relevance
“…In Felipin et al [13], who observed that the prevalence of AKI was more present in extreme preterm infants, that is, less than 28 weeks of gestational age and in PTNB less than 1500 grams like our study results.…”
Section: Resultssupporting
confidence: 86%
“…In Felipin et al [13], who observed that the prevalence of AKI was more present in extreme preterm infants, that is, less than 28 weeks of gestational age and in PTNB less than 1500 grams like our study results.…”
Section: Resultssupporting
confidence: 86%
“…This could be due to the diagnosis of AKI in that study was defined by SCr greater than 1.5 mg/dl while in this study defined AKI an absolute serum creatinine rise ≥ 0.3 mg/dL or SCr rise ≥ 1.5–1.9 × baseline SCr within 48 h and there was also differences in included study populations. Also, this study finding is higher than studies conducted in northwest Parana state (7.5%), Iran (10.68%), India (12%), and United Arab Emirates (11.6%) [ 22 , 37 39 ]. This may probably be due to study setting (institutional level) differences.…”
Section: Discussioncontrasting
confidence: 76%
“…In a case control study done by Cataldi et al with 81 neonates, it was found that 48% of babies were extreme preterm babies whereas in a retrospective study done by Felipin et al it was found that percentage of extreme preterm babies was 60%. 6,20 In the current study, it was found that 40% of the babies were having birth weight less than 1000grams, 40% of babies were having birth weight between 1000-1500 grams, and 20% were having birth weight between 1500-2500 grams.…”
Section: Studymentioning
confidence: 47%
“…In a retrospective study done by Felipin et al it was found that 60% of the babies were having birth weight of less than 1000 grams, 30% of babies were having birth weight between 1000-1500 grams; 10% of babies were having birth weight between 1500-2500 grams. 20 In this study, it was found that 31% of babies were small for gestational age (SGA). In a study done by Viswananthan et al in 2011, 41% of babies were SGA and in study done by Bolat et al it was found that 33.3% of babies were SGA.…”
Section: Studymentioning
confidence: 90%